ASSOCIATION OF SURFACTANT PROTEIN-D WITH OBESITY - Jawed, Shireen; Mannan, Nighat; Qureshi, Masood Anwar (Journal of Ayub Medical College Abbottabad, 2016)
Background: Obesity is associated with inflammatory diseases and obese individual's poses high risk for infections. Surfactant protein D (SP-D) is an important regulator of immunity and inflammation. Latest studies have suggested that it is also involved in lipid homeostasis and obese subjects have decrease concentration of SP-D as compared to normal weight peoples. The aim of the current study was to elucidate the relationship among serum SP-D and BMI. Method: This cross sectional study was performed at Dow University of health sciences (DUHS), Karachi. We analysed 90 obese and non-obese subjects for serum SP-D concentration. SP-D was estimated by ELISA. Data was analysed by SPSS 16. Mean SP-D level and demographical variables between the groups were compared by t test, Associations of SP-D with BMI investigated by regression analysis. Results: obese subjects have significant lower levels of Serum SP-D than non-obese and negatively associated with BMI in both genders (p=0.000). Conclusion: This study concluded that obese subjects have lower concentration of SP-D as compare to non-obese and there is an inverse association between the SP-D and BMI. Keywords: Surfactant Protein- D, Obesity, Total Body Mass Index (BMI), inflammatory diseases